2013
DOI: 10.1094/pdis-06-12-0590-re
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex PCR Assay for Detection ofPseudomonas syringaepv.actinidiaeand Differentiation of Populations with Different Geographic Origin

Abstract: Pseudomonas syringae pv. actinidiae is responsible for severe outbreaks of bacterial canker of kiwifruit currently occurring around the world. Although molecular detection methods have been reported, none provide complete selectivity for this pathovar or discriminate among pathogen haplotypes. Therefore, a new multiplex polymerase chain reaction (PCR) assay was developed and validated. The assay was tested on 32 P. syringae pv. actinidiae isolates and 15 non-P. syringae pv. actinidiae strains and correctly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 25 publications
2
56
0
1
Order By: Relevance
“…The newly designed primer sets amplify their correct targets in concentrations at or below 1 ng/ml for all gDNA templates, and at or below 10 pg/ml for three AFC species, which is comparable with previously reported sensitivity for multiplex assays of phytopathogenic fungi (Dreaden et al 2012;Rigotti et al 2002) and bacteria (Balestra et al 2013). The multiplex assays successfully identified AF-3 and AF-4 from pooled DNA from eight batches of freshly macerated E. interjectus and E. validus beetle heads, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…The newly designed primer sets amplify their correct targets in concentrations at or below 1 ng/ml for all gDNA templates, and at or below 10 pg/ml for three AFC species, which is comparable with previously reported sensitivity for multiplex assays of phytopathogenic fungi (Dreaden et al 2012;Rigotti et al 2002) and bacteria (Balestra et al 2013). The multiplex assays successfully identified AF-3 and AF-4 from pooled DNA from eight batches of freshly macerated E. interjectus and E. validus beetle heads, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…The NZ V-13 ICE is also present in the genome of the Chinese outbreak strain C-1, however, as previously indicated [22], [29], this region is highly divergent in the four Italian and two Chilean outbreak strains [27]. A comparison of the Italian (Mediterranean Island), Chilean (Andean Island) and the Pacific Island is depicted in Figure 6.…”
Section: Resultsmentioning
confidence: 68%
“…The origin of the current global epidemic is the subject of interest and speculation, with reports that China is the likely source [22], [27], [29]. Previous studies identified six SNPs that distinguished European from Chinese isolates [22]; upon inclusion of two Chilean isolates, nine diagnostic SNPs were identified [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically considered a minor disease, P. syringae pv. actinidiae rarely caused severe damage to kiwifruit until 2008, when a large outbreak occurred in Italy, and severe infections continue to spread to other countries (Mazzaglia et al, 2011;Chapman et al, 2012;Balestra et al, 2009Balestra et al, , 2013; Vanneste et al, 2013). In Italy, the bacterium has been shown to cause severe disease symptoms, including leaf wilting; twig or cane dieback; cankers on canes, leaders, and trunks; plant wilting; and the production of an oozing red or white exudate (Ferrante and Scortichini, 2010;Bull et al, 2011).…”
Section: Introductionmentioning
confidence: 99%